Ruang Lingkup Hukum Dalam Pasar Modal - Ardiansah, Wigi; Yansah, Yudi (Jurnal Justice Aswaja, 2023)
The scope of capital market law refers to a series of norms, regulations, and legal provisions that govern securities transaction activities and activities related to the capital market. Capital market law aims to create a fair, transparent, and efficient environment for market players, such as investors, issuers, and financial institutions. First, the scope of capital market law includes regulations related to the issuance and public offering of securities by companies. This includes the process of approval and supervision of prospectus documents and the obligation to convey accurate information to the public. In addition, capital market law regulates securities transactions and trading on the stock exchange, ensuring the creation of a fair and transparent mechanism. Second, capital market law includes investor protection. This includes the provision of clear and easy-to-understand information, as well as the application of the principle of fairness in the treatment of investors. This law also stipulates rules related to manipulative or fraudulent practices that can harm investors. Third, regulatory aspects regarding financial institutions such as securities companies, investment management companies, and stock exchanges are an integral part of the scope of capital market law. This includes licensing requirements, corporate governance, and reporting obligations. Fourth, capital market law also regulates law enforcement and sanctions for violations. This involves capital market supervisory institutions and dispute resolution mechanisms, including courts or specialized arbitration institutions. Thus, the scope of capital market law is comprehensive, covering various aspects involving market participants in order to create a stable, transparent and fair environment for all parties involved in capital market activities.